National survey of the Society for Assisted Reproductive Technology membership regarding insurance coverage for assisted reproductive technologies - Seifer, David B.; Wantman, Ethan; Sparks, Amy E.; Luke, Barbara; Doody, Kevin J.; Toner, James P.; van Voorhis, Bradley J.; Lin, Paul C.; Reindollar, Richard H. (Fertility and sterility, 2018)
To assess the attitudes of Society for Assisted Reproductive Technology (SART) members regarding expanding insurance coverage for patients seeking assisted reproductive technologies (ART) and identify some of the factors that may influence such attitudes. An anonymous online 14-question survey of SART membership; 1,556 surveys were sent through the SART Research Portal from June to December 2017. Questions were incremental in scope, beginning with expanding insurance coverage for ART for vulnerable populations (e.g., fertility preservation for cancer, couples with same recessive gene, fertility preservation for transgender individuals) to extending coverage to include patients who were uninsured for ART. Additional questions assessed attitudes about assuming some fiscal responsibility if mandated insurance were contingent on elective single-embryo transfer (eSET) and lower charges in anticipation of increased number of cases. Not applicable. Not applicable. Not applicable. Specific response to 14 survey questions. The overall response rate was 43.4% (675/1,556). A large majority (>95%) favored insurance for fertility preservation for cancer patients and for avoidance of genetic disorders; 62.3% were supportive of infertility insurance coverage for transgender patients; 78% supported expanding insurance for the broadest segment of the general uninsured population; 76.7% supported expanding insurance contingent on eSET; and 51.3% would consider expanding insurance contingent on lowering charge per cycle in general, but only 23% responded as to what lower charge would be acceptable. Three of four factors were shown by multivariable logistic regression to be predictive of attitudes willing to expand insurance: practice setting (academic > hybrid > private), practicing in a mandated state, and higher annual volume of cases (>500 cycles); these had significant increased adjusted odds ratios ranging from 1.7 to 2.9. A fourth factor, the professional role one had in the practice, was not found to be of significant predictive value. The great majority of respondents were supportive of expanding insurance for specific segments of vulnerable populations with special needs and for the population who are presently uninsured. Furthermore, the majority of respondents would consider expanding insurance coverage contingent on age-appropriate eSET but have concerns about reduced reimbursement. Those most likely to be willing to expand insurance are those who practice in an academic setting or a mandated state and/or have a high annual volume of cases. Encuesta nacional de los miembros de la Sociedad para la Técnica de Reproducción Asistida relativa a la cobertura de seguro médico para las técnicas de reproducción asistida Evaluar la actitud de los miembros de la Sociedad para la Técnica de Reproducción Asistida (SART) relativa a la ampliación de la cobertura del seguro médico para pacientes que necesitan técnicas de reproducción asistida (TRA) e identificar algunos de los factores que podrían influenciar esa actitud. Se entregó una encuesta anónima on-line con 14 preguntas a los miembros de la SART; 1.556 encuestas se enviaron a través del portal de investigación de la SART entre junio y diciembre 2017. Las preguntas cubrieron desde la ampliación del seguro médico para TRA en la población vulnerable (ejemplo preservación de fertilidad en cáncer, parejas que comparten los mismos genes recesivos, preservación de fertilidad en personas transgénero) hasta la ampliación del seguro para los pacientes que no tienen cobertura médica para TRA. Cuestiones adicionales evaluaron la actitud sobre asumir alguna responsabilidad fiscal si el seguro obligatorio estuviera supeditado a la transferencia de un único embrión electivo (eSET) y menores cargos, previendo un aumento en el número de casos. No aplica No aplica No aplica La respuesta específica a las 14 preguntas. La tasa de respuesta general fue de 43,4% (675/1.556). Una amplia mayoría (>95%) se inclinó por la ampliación del seguro para la preservación de fertilidad para las pacientes oncológicas y para evitar las enfermedades genéticas; el 62,3% apoyó la cobertura de infertilidad en pacientes transgénero; el 78% apoyó la ampliación del seguro a un amplio segmento de la población sin seguro; el 76,7% respondió afirmativamente a la ampliación del seguro para eSET; el 51,3% consideraría ampliar los contingentes del seguro disminuyendo los costes por ciclo en general, pero sólo el 23% respondieron que cuál sería el menor cargo aceptable. Mediante regresión logística multivariable, tres o cuatro factores demostraron ser predictivos para una actitud favorable a la ampliación del seguro: tipo de centro médico (docente > híbrido> privado), ejerciendo en un centro regido por el estado y con el volumen anual más alto de casos (>500 ciclos); estos tuvieron unas razones de verosimilitud aumentadas significativamente que oscilaron entre 1,7 y 2,9. Un cuarto factor, el rol profesional que se tuviese en la institución, no se objetivó como valor predictivo significativo. Una amplia mayoría de los participantes en la encuesta apoyan la ampliación del seguro para sectores específicos vulnerables de la población con necesidades especiales y para la población actualmente sin seguro. Además, la mayoría de los participantes considerarían la ampliación del seguro para eSET en edades apropiadas, pero con preocupación por el reembolso reducido. Aquellos más abiertos a la ampliación del seguro son aquellos que trabajan en centros académicos o en un centro regido por el estado y/o tienen un volumen anual de casos alto.